Combination of orthodontic movement and periodontal therapy for full root coverage in a miller class iii recession: A case report with 12 years of follow-up - De Molon, Rafael Scaf [UNESP]; De Avila, Érica Dorigatti [UNESP]; De Souza, João Antonio Chaves [UNESP]; Nogueira, Andressa Vilas Boas [UNESP]; Cirelli, Carolina Chan [UNESP]; Cirelli, Joni Augusto [UNESP] (FapUNIFESP (SciELO), 2012)
One of the main purposes of mucogingival therapy is to obtain full root coverage. Several treatment modalities have been developed, but few techniques can provide complete root coverage in a class III Miller recession. Thus, the aim of this case report is to present a successful clinical case of a Miller class III gingival recession in which complete root coverage was obtained by means of a multidisciplinary approach. A 17-year-old Caucasian female was referred for treatment of a gingival recession on the mandibular left central incisor. The following procedures were planned for root coverage in this case: free gingival graft, orthodontic movement by means of alignment and leveling and coronally advanced flap (CAF). The case has been followed up for 12 years and the patient presents no recession, no abnormal probing depth and no bleeding on probing, with a wide attached gingiva band. A compromised tooth with poor prognosis, which would be indicated for extraction, can be treated by orthodontic movement and periodontal therapy, with possibility of 100% root coverage in some class III recessions.
Keywords: Connective tissue graft; Gingival recession; Multidisciplinary approach; Orthodontics